A Dual Plasmonic Photoelectrode System for Visible‐Light Photocatalysis. Issue 4 (25th February 2020) - Nishi, Hiroyasu; Miyake, Koji; Kao, Kun‐Che; Tatsuma, Tetsu
Abstract: Plasmonic photocathodes based on plasmon‐induced charge separation (PICS) were prepared by depositing an Au nanoparticle (AuNP) ensemble on a transparent electrode and coating it with compact TiO2 . Its PICS efficiency was improved by coating it further with porous TiO2 or introducing a NiO blocking layer as an underlayer of the AuNP ensemble. The former photocathode was modified further with Pt co‐catalyst nanoparticles, and combined with a PICS photoanode fabricated by depositing a AuNP ensemble on compact TiO2 and coating it with a Ni(OH)2 charge accumulation layer. The dual plasmonic photoelectrode system thus obtained exhibited a higher efficiency than the sum of the efficiencies of the single photoanode and single photocathode. Abstract : A dual photoelectrode system based on plasmon‐induced charge separation (PICS) was developed by combining a PICS photoanode with a PICS photocathode. The dual PICS system exhibited a higher photocatalytic activity than the sum of the activities of the single photoanode and single photocathode.